2009
DOI: 10.1038/bmt.2009.172
|View full text |Cite
|
Sign up to set email alerts
|

Lack of prompt expansion of cytomegalovirus pp65 and IE-1-specific IFNγ CD8+ and CD4+ T cells is associated with rising levels of pp65 antigenemia and DNAemia during pre-emptive therapy in allogeneic hematopoietic stem cell transplant recipients

Abstract: Rising levels of cytomegalovirus (CMV) DNAemia and/or pp65 antigenemia have been observed during pre-emptive ganciclovir therapy in patients undergoing allogeneic hematopoietic stem cell transplantation (allo-SCT). We assessed the incidence of this event in our series, and investigated whether its occurrence was associated with an impairment in the CMV-specific T-cell response. A total of 36 allo-SCT recipients experienced one or more episodes of active CMV infection (n ¼ 68) that were preemptively treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 17 publications
1
57
0
Order By: Relevance
“…In contrast, the levels of CMV (AD169)-specific IgGs measured by CLIA were not predictive of the occurrence of CMV DNAemia. In our opinion, if AbNEIs displayed a relevant role in conferring protection against CMV viraemia, the opposite phenomenon would be expected to occur, as has been shown for CMV-specific functional T-cells Tormo et al, 2010aTormo et al, , b, 2011. Several non-mutually exclusive explanations may account for this finding.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, the levels of CMV (AD169)-specific IgGs measured by CLIA were not predictive of the occurrence of CMV DNAemia. In our opinion, if AbNEIs displayed a relevant role in conferring protection against CMV viraemia, the opposite phenomenon would be expected to occur, as has been shown for CMV-specific functional T-cells Tormo et al, 2010aTormo et al, , b, 2011. Several non-mutually exclusive explanations may account for this finding.…”
Section: Discussionmentioning
confidence: 71%
“…Monitoring of plasma CMV DNAemia was performed once a week using a real-time PCR assay (CMV real-time PCR or Abbott RealTime CMV; Abbott Molecular) (Clari et al, 2013;Giménez et al, 2014;Gimeno et al, 2008). Patients were treated pre-emptively with antivirals as described previously Tormo et al, 2010aTormo et al, , b, 2011. CMV DNAemia (active CMV infection) was defined as the detection of any level of CMV DNA in plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Type B episodes were those in which rising levels of CMV DNAemia (increases Xfive-fold) were demonstrated after the implementation of antiviral therapy. 8 As shown in Table 1, the demographic and clinical characteristics of patients in both groups were not significantly different. As shown in Table 2, the incidence rate of episodes of active CMV infection and that of recurrent episodes occurred more frequently in patients in group I than in those in group II, though statistical significance was not reached.…”
mentioning
confidence: 94%
“…[34][35][36] Lack of T cell immunity against CMV is associated with an increased risk of late onset/recurrent CMV antigenemia and CMV disease. 21,[23][24][25][26][27][28][29] In EBV and ADV infections, importance of T cell immunity against was also reported. [37][38][39] Therefore, if T cell immunity is found to be insufficient in patients with viral reactivation, adoptive immunotherapy to enhance T cell reconstitution could be an option to consider in order to treat or prevent the development of endorgan disease (Fig.…”
Section: Importance Of T Cells Against Viral Infectionsmentioning
confidence: 99%
“…In terms of viral infections, it is well established that T cells play an important role. [21][22][23][24][25][26][27][28][29][30] In terms of mold infections, innate immunity alone was considered important historically in the control of mold infections. However, recent studies found that adaptive immunity, in particular Th1 cells, was relevant in the control of aspergillus infections.…”
Section: Introductionmentioning
confidence: 99%